2020
DOI: 10.1186/s12876-020-01240-z
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of advanced fibrosis in elderly patients with biopsy-confirmed nonalcoholic fatty liver disease: the GOASIA study

Abstract: Background: The Gut and Obesity in Asia (GOASIA) Workgroup was formed to study obesity and gastrointestinal diseases in the Asia Pacific region. We aimed to 1) compare the characteristics of elderly (i.e. age ≥ 60) vs. nonelderly patients with biopsy-proven nonalcoholic fatty liver disease (NAFLD); 2) identify predictors of advanced fibrosis in elderly patients with NAFLD; and 3) assess the performance of non-invasive fibrosis scores in the prediction of advance fibrosis in the elderly population. Methods: We … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 29 publications
0
32
1
3
Order By: Relevance
“…In our study, the advanced stage of fibrosis was associated with advanced age which is consistent with other previous studies [ 11 - 12 ]. A possible explanation is increased affiliation of risk factors like hypertension, diabetes mellitus type II, and/or obesity with age [ 13 ]. Also, according to “the free radical theory of aging”, the reactive oxygen species generated cannot be nullified due to impaired antioxidant defence system in aged people which elevates oxidative stress level thus causing alteration in cell growth and tumour suppressor gene [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the advanced stage of fibrosis was associated with advanced age which is consistent with other previous studies [ 11 - 12 ]. A possible explanation is increased affiliation of risk factors like hypertension, diabetes mellitus type II, and/or obesity with age [ 13 ]. Also, according to “the free radical theory of aging”, the reactive oxygen species generated cannot be nullified due to impaired antioxidant defence system in aged people which elevates oxidative stress level thus causing alteration in cell growth and tumour suppressor gene [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…A total of 1370 MAFLD patients (78.5%) exhibited a low cut-off index (COI) (<1.30), 357 (20.5%), exhibited an indeterminate COI (1.30–2.67), and 18 (1.0%) exhibited a high COI (>2.67) [ 92 ]. Among 5410 Japanese MAFLD patients who were diagnosed by health checkups, 87.4% exhibited low COI (<1.45), 12.1% exhibited an indeterminate COI (1.45–3.26), and 0.5% exhibited a high COI (>3.26) [ 93 ]. On data of 576 MAFLD with biopsy proven MAFLD from JSG-NAFLD, 336 (58.3%) exhibited low COI (<1.45), 31.4% exhibited an indeterminate COI (1.45–3.26), and 59 (10.2%) exhibited a high COI (>3.26) [ 16 ].…”
Section: Distribution Of Fib-4 Index In Mafld Populationmentioning
confidence: 99%
“…In a recent study, these cut-offs were tested and the low specificity confirmed in elderly Asian patients. 122 By using the new age-adjusted cut-offs proposed by McPherson, specificity was increased albeit at the cost of lower sensitivity. Therefore, more studies are necessary to understand how to employ fibrosis scoring systems while taking the patient’s age into account.…”
Section: Diagnosis and Screening Of Nafldmentioning
confidence: 99%
“…Initial studies assessing the utility of these scores focused primarily on middle-aged patients, did not include elderly patients or failed to determine the diagnostic cut-off values in this cohort of patients. [119][120][121][122] Because both NFS and FIB-4 take age into account, there is an inflation of the score in the elderly due to the inclusion of this parameter by itself. As a result, more patients are considered to be intermediate-risk in virtue of their age, which increases the false positive rate.…”
Section: Scoring Systemsmentioning
confidence: 99%